The outcomes of blastocyst versus cleavage stage embryo biopsy for preimplantation genetic testing for monogenic diseases - Marom Haham, Lilach; Aizer, Adva; Arad, Almog; Haas, Jigal; Lebovitz, Oshrit; Zilberberg, Eran; Nahum, Ravit; Orvieto, Raoul (Frontiers in Endocrinology, 2025)
In recent years, the application of blastocyst biopsy in PGT has been gradually rising, mainly due to the assumed detrimental effect of blastomere biopsy on the embryo implantation potential and the widespread application of PGT for aneuploidy. In contrast to complete chromosomal testing (CCT) cycles, for which trophectoderm (TE) biopsy has become the well-established preferred method due to higher diagnostic reliability, evidences for the purpose of PGT-M are still lacking. Therefore, we conducted a retrospective cohort study including 147 PGT-M cycles with at least eight high quality embryos (HQE) suitable for biopsy at the cleavage stage, 83 and 64 in the blastocyst and cleavage stage biopsy groups, respectively. Our results showed no significant differences in implantation rates (32.8% vs. 33.6%, p=0.9), clinical pregnancy rates (CPR) per transfer (30.3% vs. 33.0%, p=0.7), as well as cumulative CPR (46.2% vs. 38.3%, p=0.4). This study is the largest so far, demonstrating that blastocyst biopsy has higher cost-effectiveness over cleavage stage biopsy in good prognosis patient population. Moreover, our data is the first to show that blastomere biopsy does not compromise the reproductive outcomes, which merits further investigation regarding its cost-effectiveness in the poor prognosis patient population, having a small number of embryos for biopsy and transfer. Further large prospective randomized studies are needed to elucidate the preferred biopsy strategy in specific patient populations in order to provide a tailored treatment that will ensure the best prognosis for each patient.